Implementasi Pemanfaatan Limbah Bambu Sebagai Peluang Usaha Kerajinan Tangan Kelurahan Kepanjen Kidul Kota Blitar - Dewi Puspa Arum; Indah Sari Dwi; Usamah Abdul Haq; Herlangga Turna Cahyantoro; M. Wesla Dhifayana S.; Algi Ardiyansyah; Rendi Cahya Saputra (Universitas Kristen Indonesia Toraja, 2023)
Bamboo waste is a type of waste or waste generated by development projects that still has the potential to be utilized, one of which is as a raw material in the manufacture of handicraft products. The use of bamboo waste as a raw material in the manufacture of handicrafts is still not optimal. The potential of bamboo waste as a raw material for making handicrafts is still wide open. The method used in this journal is first, an initial survey by identifying the potential for bamboo waste in the Kepanjenkidul Village. Second, collecting data through observation and interviews. Third, data analysis using quantitative and qualitative methods. Fourth, product development which aims to develop handicraft products from product waste. Fifth, evaluation of results to evaluate the success of implementing bamboo waste utilization. The MBKM 25 Thematic Community Service Group provides assistance and development of MSMEs in the form of implementing community service activities. The activity is to assist and assist in carrying out the production process to the packaging process.